Pengaruh Pelatihan Terhadap Prestasi Kerja Pegawai Kantor Kecamatan Sangalla Kabupaten Tana Toraja - Taufik, Imran; Guntur, Ihsan; Misbahuddin; Akil, Nasriah; Abdullah (Jurnal Online Manajemen ELPEI, 2025)
This study aims to determine the effect of training on employee performance. This type of research uses a quantitative type, while the sample taken is 42 employees. The simple linear regression analysis technique used in this study with validity testing, reliability testing, and hypothesis testing. The results of the study have been tested for validity and are declared valid with the smallest score of the return on capital indicator of 0.362 and the highest score of work performance (Y) of 0.720 is declared valid. The results of the reliability test that with both variables exceeding Cronbach Alpha> 0.6 so that the study is said to be reliable or worthy of being continued. The results of the study partially show that work training has a positive and significant effect on work performance. With a significance level of 0.002 smaller than 0.05 (0.002 <0.05). Then for the t test with a significance level of 0.05, the value of t1 is obtained: 0.025 = 2.02108 (based on the value of the t statistic table with v = 40 and a significance level = 0.025) while for t count, the value obtained from the data processing that has been done is 3.349 for that it can be concluded that t count> t table, then H0 is rejected and H1 is accepted. For the coefficient of determination based on the existing data, the coefficient of determination (R2) is 0.219. This means that job training has an influence of 21.9% on work performance at the Sangalla District office.